2022
DOI: 10.1097/cm9.0000000000002233
|View full text |Cite
|
Sign up to set email alerts
|

A zero-sum game or an interactive frame? Iron competition between bacteria and humans in infection war

Abstract: Iron is an essential trace element for both humans and bacteria. It plays a vital role in life, such as in redox reactions and electron transport. Strict regulatory mechanisms are necessary to maintain iron homeostasis because both excess and insufficient iron are harmful to life. Competition for iron is a war between humans and bacteria. To grow, reproduce, colonize, and successfully cause infection, pathogens have evolved various mechanisms for iron uptake from humans, principally Fe3+-siderophore and Fe2+-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 103 publications
0
10
1
Order By: Relevance
“…Together, these mechanisms limit the iron available to pathogens and hence inhibit bacterial reproduction in the body. 44 In this study, no polymorphism of exon 15 D543 was found. These results are in line with research in Surabaya, Indonesia.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Together, these mechanisms limit the iron available to pathogens and hence inhibit bacterial reproduction in the body. 44 In this study, no polymorphism of exon 15 D543 was found. These results are in line with research in Surabaya, Indonesia.…”
Section: Discussioncontrasting
confidence: 49%
“…The human body also decreases the absorption of iron from the intestine. Together, these mechanisms limit the iron available to pathogens and hence inhibit bacterial reproduction in the body 44 …”
Section: Discussionmentioning
confidence: 99%
“…Fe is the most abundant trace element in the human body and plays a vital role in human health . Fe-based biomaterials are generally highly biocompatible.…”
Section: Introductionmentioning
confidence: 99%
“…Fe is the most abundant trace element in the human body and plays a vital role in human health. 18 Fe-based biomaterials are generally highly biocompatible. Iron oxide nanoparticles have been approved by the US Food and Drug Administration (FDA) for clinical use to treat iron deficiency anemia and as an MRI contrast agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation